Transformasi Perpajakan Digital Di Indonesi : Kajian Eksplanatori - Kadlina Kadlina; Agus Munandar (Akuisisi : Jurnal Akuntansi, 2026)
This explanatory research seeks to investigate the underlying reasons or factors that drive taxation on online transactions. In the digital era, online transactions have become increasingly pervasive, allowing companies to generate revenue from other countries where they do not maintain a physical presence. This paper adopts explanatory approach, utilizing a comprehensive literature review to identify the factors influencing the implementation of online transaction taxation. The findings reveal several critical factors, including the COVID-19 pandemic, cross-border electronic transaction, the communication strategies between tax authorities and businesses or consumers, and regional cooperation. The interplay of these factors can enhance the effectiveness of digital taxation in Indonesia.